Penegakan Hukum terhadap Pelaku yang melakukan Perbantuan dalam Tindak Pidana Terorisme - Imanuel Galih Tri Buwono; Sudarto Sudarto (FOCUS, 2026)
Terrorism is classified as an extraordinary crime, not only because it causes direct harm but also because of its potential to undermine national security and disrupt societal order. While the principal perpetrators of terrorism are often the focus, those who assist in such crimes—whether by providing logistical support, shelter, or facilitating the execution of the act—play a crucial role in sustaining terrorist networks. This research analyzes the legal framework governing the role of accomplices in terrorist acts under Indonesia’s Law No. 5 of 2018 and examines the law enforcement practices based on the court decision in Case No. 1114/Pid.Sus/2023/PN Jkt.Utr. By employing a normative juridical approach, the study finds that the law equates the punishment of an accomplice to that of the principal perpetrator, which strengthens deterrence but may obscure the principle of proportionality in sentencing. The study further highlights the importance of clear and differentiated legal provisions for accomplices to avoid overcriminalization and ensure justice, as well as the role of the judiciary in interpreting these provisions with fairness and consistency. Finally, recommendations are made for improving legal certainty and the effectiveness of counterterrorism measures in Indonesia